Prognostic Value of Platelet-to-Lymphocyte Ratio Combined with CHA2DS2-VASc Score for Nonvalvular Atrial Fibrillation Induced Cardiogenic Cerebral Embolism - Fan Q; Gao L; Wang Z; Ndjana Lessomo FY; Wang G (Dove Medical Press, 2023)
Qian Fan,1,* Ling Gao,1,* Zhiquan Wang,2,* Fabrice Yves Ndjana Lessomo,2 Gang Wang1 1Department of Cardiology, The Second Affiliated Hospital of Shandong First Medical University, Taian, Shandong, People's Republic of China; 2Department of Cardiology, Zhongnan Hospital of Wuhan University, Wuhan, Hubei, People's Republic of China*These authors contributed equally to this workCorrespondence: Gang Wang, Email cardio9090@sina.comAim: To determine the predictive significance of the platelet-to-lymphocyte ratio (PLR) combined with the CHA2DS2-VASc score for cardiogenic cerebral embolism (CCE) in patients with nonvalvular atrial fibrillation (NVAF).Methods: A total of 553 patients with NVAF were included in this retrospective study. The general data, PLR, CHA2DS2-VASc score and echocardiography indicators were compared. The risk factors for CCE and the predictive value of PLR and CHA2DS2-VASc were analyzed. Stratified analysis was performed based on the cut-off value. Least absolute shrinkage and selection operator (LASSO) regression analysis was utilized to build a model. The relationship between risk score and different anticoagulants was evaluated.Results: Multiple regression analysis showed hypertension (OR=3.95, 95% CI=2.12- 7.35, p=1.40× 10− 5), diabetes mellitus (OR=2.95, 95% CI=1.57- 5.58, p=7.65× 10− 4), PLR (OR=1.01, 95% CI=1.00- 1.01, p< 10− 6), creatinine level (OR=1.01, 95% CI=1.00- 1.02, p=7.44× 10− 3), left atrial diameter (LAD) (OR=1.90, 95% CI=1.13- 3.19, p=1.51× 10− 2), ejection fraction (EF) (OR=0.93, 95% CI=0.87- 0.98, p=8.06× 10− 3) and CHA2DS2-VASc score (OR=3.79, 95% CI=2.95- 4.85, p< 10− 6) were independent risk factors for CCE. A one-way linear analysis also showed the above seven indexes were significantly correlated with CCE (F=56.4, p< 10− 6). The area under the receiver operating characteristic (ROC) curve of PLR and CHA2DS2-VASc score was 0.760 (95% CI:0.721- 0.800), and 0.855 (95% CI: 0.824- 0.886), respectively. Pearson correlation analysis showed that PLR was correlated with CHA2DS2-VASc score (r=0.331, p< 10− 6). Stratified analysis indicated there was a positive correlation between different risk group (p< 10− 6). Using the LASSO model, a composite indicator displayed differential power for distinguishing CCE with an AUC value of 0.884 (95% CI: 0.857- 0.911). Patients with dabigatran and rivaroxaban exhibited higher risk score than those with warfarin (warfarin vs dabigatran, p=1.40× 10− 2; warfarin vs rivaroxaban p=3.00× 10− 3).Conclusion: PLR and CHA2DS2-VASc score are independent risk factors for CCE with NVAF, and the combination of the two indices can improve the prediction of CCE.Keywords: NVAF, CCE, PLR, CHA2DS2-VASc score, LASSO model